1997
DOI: 10.1002/art.1780400310
|View full text |Cite
|
Sign up to set email alerts
|

Increased rates of fibromyalgia following cervical spine injury. A Controlled study of 161 cases of traumatic injury

Abstract: Objective. To study the relationship between cervical spine injury and the development of fibromyalgia syndrome (FMS).Methods. One hundred two patients with neck injury and 59 patients with leg fractures (control group) were assessed for nonarticular tenderness and the presence of FMS. A count of 18 tender points was conducted by thumb palpation, and tenderness thresholds were assessed by dolorimetry at 9 tender sites. All patients were interviewed about the presence and severity of neck and FMS-related sympto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
164
1
4

Year Published

1998
1998
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 303 publications
(171 citation statements)
references
References 17 publications
2
164
1
4
Order By: Relevance
“…Wolfe reported a 40% prevalence of neck injury and a 31% prevalence of back injury in a series of patients with fibromyalgia [54]. Buskila et al reported that the incidence of fibromyalgia was 13 times greater following neck injury than following lower extremity injury [14].…”
Section: Discussionmentioning
confidence: 99%
“…Wolfe reported a 40% prevalence of neck injury and a 31% prevalence of back injury in a series of patients with fibromyalgia [54]. Buskila et al reported that the incidence of fibromyalgia was 13 times greater following neck injury than following lower extremity injury [14].…”
Section: Discussionmentioning
confidence: 99%
“…These data suggest that evidence of vulnerability to PTSD in the immediate aftermath of a MVC predicts subsequent development of chronic WAD. Evidence that a subset of those with neck pain after MVC progresses to develop fibromyalgia (72) suggests that WAD and FM may be linked and that vulnerability to develop PTSD after MVC may also predict the development of fibromyalgia. These data suggest the testable hypothesis that factors which predict vulnerability to PTSD in prospective studies will also predict vulnerability to WAD and fibromyalgia.…”
Section: Association Between Ptsd Symptoms and Wad Symptoms During Wamentioning
confidence: 99%
“…This can be seen in our comparison of articles by number of citations per year. Carragee et al 6 article has an average citation of 76.6 per year compared with Frankel et al, 7,25,68 . We see articles on cervical disc arthroplasty advancing significantly when we rank by average per year.…”
mentioning
confidence: 93%